Sustainable tourism from the perspective of tourists in Nganjuk Indonesia - Supheni, Indrian; Ivada, Elvia; Novianti, Grevita Elma; Wiwin, Wiwin (Goodwood Publishing, 2023)
Purpose: This study aims to analyze tourists' perspectives regarding the sustainability of four tourism destinations, namely Sedudo Waterfall, Roro Kuning, TRAL, and Margo Tresno Cave in Nganjuk East Java, Indonesia. Moreover, this study attempts to reveal tourists' sustainability awareness based on the triplebottom-line concept and which dimensions are considered the most important for tourists. Research Methodology: Data were obtained from a survey of visitors (16 years old and over) to the four tourist objects in Nganjuk. Furthermore, this study utilized Principal Component Analysis (PCA) and ANOVA tests to evaluate the differences between types of tourists and their views on sustainability. Results: The number of types of tourists found in the Nganjuk tourist destination was change, amusement, rupture, interest, and dedication. The ANOVA test results show a different tourist perception of sustainability issues from the five types of tourists in Nganjuk. Limitations: This study involved only young respondents who did not consider tourists beyond a young age. In addition, this study focused only on one regency in Indonesia. Contributions: To create a tourism industry that can last and protect the environment, the vital role of tourists cannot be ignored. This research makes a theoretical contribution by expanding the theory to explain aspects that have never been studied before regarding tourists' understanding of the sustainability issue in the tourism sector. Novelty: This study is one of the first to discuss tourists' perceptions of sustainability issues in the Indonesian context.